Organic Agriculture and Animal Husbandry in Bayburt Current Status - Bülent Bayraktar (Turkish Journal of Agriculture: Food Science and Technology)
Nowadays, organic products are produced without the use of chemical additives in natural conditions is constantly increasing every day. However, the new organic food market and organic production evaluation and development of areas with high potential for the formation of the subject is of great importance. In this context, bayburt, accommodates very suitable ecological conditions for organic production. A significant portion of the surface area agricultural land with meadows and pastures. In addition, minimal amount of chemical and industrial facilities is one of the provinces where the use of the drug is low. Areas with high potential in the development and evaluation of the institutions has an important role. However, the institutions, which is determined by the strategic objectives, resources and competencies varies according to. In this review, Bayburt province implemented in joint projects, training activities, and the development of organic production of agricultural subsidies, it is observed that Speed has a restorative effect. So it has not made production, but with high potential of supporting the development of organic agriculture and animal husbandry products will make a major contribution to the development of the current expected.